2008
DOI: 10.1007/s11432-008-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved empirical DC I–V model for 4H-SiC MESFETs

Abstract: A novel empirical large signal direct current (DC) I-V model is presented considering the high saturation voltage, high pinch-off voltage, and wide operational range of drain voltage for 4H-SiC MESFETs. A comparison of the presented model with Statz, Materka, Curtice-Cubic, and recently reported 4H-SiC MESFET large signal I-V models is made through the Levenberg-Marquardt method for fitting in nonlinear regression. The results show that the new model has the advantages of high accuracy, easily making initial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The threshold voltage decreases with the increase in channel doping. This decrease can be explained by equation (2). As the doping increases, V p0 increases, and this results in the decrease of the threshold voltage, as shown from equation (1).…”
Section: Device Simulation and Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…The threshold voltage decreases with the increase in channel doping. This decrease can be explained by equation (2). As the doping increases, V p0 increases, and this results in the decrease of the threshold voltage, as shown from equation (1).…”
Section: Device Simulation and Analysismentioning
confidence: 90%
“…, (2) V T is the threshold voltage, V bi is the built-in potential, V p0 is the pinch off voltage, q is the charge of an electron, N D is the channel doping, a is the channel thickness, and ε is the dielectric constant of 3C-SiC. The Mathcad simulation has shown that the threshold voltage of this device is about -4.5V.…”
Section: Device Simulation and Analysismentioning
confidence: 96%
See 1 more Smart Citation